Effect of Mouriri pusa extracts on experimentally induced gastric lesions in rodents: Role of endogenous sulfhydryls compounds and nitric oxide in gastroprotection - Andreo, Marcio Adriano; Rodriguez Ballesteros, Katia Veronica; Hiruma-Lima, Clelia Akiko; Machado da Rocha, Lucia Regina; Monteiro Souza Brito, Alba Regina; Vilegas, Wagner [UNESP] (Elsevier B.V., 2006)
Several plants are used in folk medicine to treat gastrointestinal disorders. Mouriri pusa Gardn. (Melastomataceae) is a medicinal plant commonly used in the central region of Brazil against gastric ulcer. Two organic extracts methanolic (MeOH) and dichloromethane (DCM) obtained by sequential extraction from the leaves of Mouriri pusa were evaluated for their ability to protect the gastric mucosa against injuries caused by necrotizing agents (0.3 M HCl/60% EtOH, absolute ethanol, non-steroidal anti-inflammatory drug, stress and pylorus ligature) in mice and rats. The best results were obtained after pretreatment with MeOH extract whereas the DCM extract did not show the same significant antiulcerogenic activity. No acute toxicity was observed in animals treated with 5 g/kg, p.o. of MeOH extract. The mechanism involving the antiulcerogenic action of MeOH extract seemed to be related to NO generation and also suggested the effective participation of endogenous sulfhydryl group in the gastroprotective action. Phytochemical investigation of the MeOH extract of Mouriri pusa yielded tannins, flavonoids and (-)-epicatechin. The presence of these phenolic compounds probably would explain the antiulcerogenic effect of the polar extract of Mouriri pusa leaves. (c) 2006 Elsevier B.V.. All rights reserved.
Keywords: Mouriri pusa; Melastomataceae; tannins; flavonoids; antiulcerogenic activity